2002
DOI: 10.1136/bmj.324.7344.1006
|View full text |Cite
|
Sign up to set email alerts
|

Decision making processes in people with symptoms of acute myocardial infarction: qualitative study

Abstract: Objective To identify the themes that influence decision making processes used by patients with symptoms of acute myocardial infarction. Design Qualitative study using semistructured interviews. Setting Two district hospitals in North Yorkshire. Participants 22 patients admitted to hospital with confirmed second, third, or fourth acute myocardial infarction. Main outcome measure Patients' perceptions of their experience between the onset of symptoms and the decision to seek medical help. Results Six main theme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
132
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(151 citation statements)
references
References 16 publications
14
132
1
4
Order By: Relevance
“…The transient nature of their symptoms, including chest pain, was frequently confusing for the participants. These findings accord with those of a previous investigation that showed the help-seeking decision-making process of people admitted to hospital with an AMI to be a complex interaction of knowledge and experience, beliefs, emotions, and the context of the event (Pattenden, Watt, Lewin, & Stanford, 2002). Pattenden et al (2002) found that patients experiencing the symptoms of AMI were often reluctant to relinquish control to healthcare professionals, and frequently attributed their symptoms to a benign, non-cardiac cause.…”
Section: Beyond the Masculine-feminine Binarysupporting
confidence: 90%
See 2 more Smart Citations
“…The transient nature of their symptoms, including chest pain, was frequently confusing for the participants. These findings accord with those of a previous investigation that showed the help-seeking decision-making process of people admitted to hospital with an AMI to be a complex interaction of knowledge and experience, beliefs, emotions, and the context of the event (Pattenden, Watt, Lewin, & Stanford, 2002). Pattenden et al (2002) found that patients experiencing the symptoms of AMI were often reluctant to relinquish control to healthcare professionals, and frequently attributed their symptoms to a benign, non-cardiac cause.…”
Section: Beyond the Masculine-feminine Binarysupporting
confidence: 90%
“…These findings accord with those of a previous investigation that showed the help-seeking decision-making process of people admitted to hospital with an AMI to be a complex interaction of knowledge and experience, beliefs, emotions, and the context of the event (Pattenden, Watt, Lewin, & Stanford, 2002). Pattenden et al (2002) found that patients experiencing the symptoms of AMI were often reluctant to relinquish control to healthcare professionals, and frequently attributed their symptoms to a benign, non-cardiac cause. As other researchers have described (Clark, 2001;Dracup et al, 1995;Galdas et al, 2007;Pattenden et al, 2002;), several participants in our study had waited until their attempts at self-treatment had failed, or their symptoms were viewed as being persistent or more severe, until they decided that their condition was serious and they required health care.…”
Section: Beyond the Masculine-feminine Binarysupporting
confidence: 90%
See 1 more Smart Citation
“…37 A recent review of the public's awareness of stroke found that although between 27% and 100% of participants stated that they would call the EMSs, only 18% had actually done so. 26 Emotional response and context appear to be influential in deciding to seek emergency help.…”
Section: Discussionmentioning
confidence: 99%
“…While there is a broad literature on men's overall healthseeking behavior (Kaur et al, 2007;O'Brien et al, 2005;Pattenden, Watt, Lewin, & Standford, 2002), much less is known about their sexual health seeking. Sexual health is an important arena in which to study men's health seeking behaviors as their decisions about whether or not to seek care in this area affects not only their own health, but that of their sex partners as well.…”
mentioning
confidence: 99%